The Relationship Between Atrial Cardiopathy Biomarkers and Prognosis of Patients With Embolic Stroke of Undetermined Source - Ning, Yuye; Wei, Meng; Song, Wenfeng; Luo, Guogang (Frontiers in Cardiovascular Medicine, 2022)
Objective: To compare the proportion of atrial cardiopathy in patients with embolic stroke of undetermined source (ESUS) and other non-cardiac strokes, and to evaluate the prognostic value of atrial cardiopathy biomarkers in ESUS patients. Methods: This retrospective study enrolled ischemic stroke patients from January 2018 to April 2020 in single stroke center, and compared the proportion of atrial cardiopathy in 1) ESUS group, 2) large artery atherosclerosis (LAA) group, and 3) small-vessel occlusion (SVO) group. Then it compared the baseline characteristics between ESUS patients with atrial cardiopathy and cardioembolism (CE) group. The relationship was also compared between the biomarkers of atrial cardiopathy and prognosis in ESUS patients. Results: In total 316 patients with ischemic stroke were included, including 105 (33.23%) ESUS, 84(26.58%) LAA, 73(23.10%) SVO and 54(17.09%) CE. Among these patients, ESUS patients were younger, and had lower triglyceride, lower low-density lipoprotein than non-ESUS group. The proportion of atrial cardiopathy in ESUS group was higher than LAA group or SVO group (42.86% vs. 17.86% vs. 8.22%, P<0.001). Compared with non-atrial cardiopathy group, atrial cardiopathy patients were older, had lower EF value, larger left ventricular diameter, longer PR interval. Among 105 ESUS patients, 11(10.78%) cases died, 32 (31.37%) cases had poor functional outcome (mRS>2). In the multivariable model, the risk factor associated with death risk of ESUS patients was NT-proBNP >250 pg/mL (P=0.025, HR=4.626, 95%CI:1.212-17.652) after a 1-year follow-up. Conclusions: Atrial cardiopathy is more common in ESUS patients, and the characteristics of ESUS patients with atrial cardiopathy are similar to those in CE patients. NT-proBNP>250 pg/mL is related to the risk of death in ESUS patients.